Effect of heat generation on dynamics of cutting process - Vilor L. Zakovorotny; Irina A. Vinokurova (Advanced Engineering Research, 2017)
Introduction. One of the mechanisms causing the loss of balance stability in the dynamic cutting system is specified by the forces-processing speed relation. Again, the forces-speed relation is explained by the temperature variation associated with the release of energy in the cutting zone. Irreversible transformations in the cutting area (and, consequently, the temperature) not only affect the stress-strain behavior of the cutting zone material, but results in the formation of various dissipative structures in the primary plastic flow areas, and the tool face-turnings contact. In this case, all changes in the cutting area properties depending on the heat generation and transfer occur in the course of time. Materials and Methods. A system mathematical model is given; the problem of the thermodynamic subsystem effect on the forming movement trajectories stability and on the attracting sets made up in the neighborhood of these trajectories is considered. And examples of the thermodynamic subsystem effect on the cutting system dynamics in general are given. Research Results. In all well-known papers, the dynamic cutting system is examined as a mechanical subsystem which coordinates of state in no way depend on the coordinates of the thermodynamics subsystem. In contrast to the known studies, the results of investigating interconnected thermodynamic and mechanical subsystems are given here. The primary focus is on the dynamic cutting system properties. The change in these properties is considered depending on the transient processes in the mechanical and thermodynamic subsystems. Their interrelation is shown through the change in parameters depending on temperature. The variation of chipping pressure on the tool face caused by irreversible energy transformations in the cutting area is taken into account. Besides, temperature tool deformations are considered. Thus, interference of the mechanical and thermodynamic subsystems is examined. Discussion and Conclusions. Irreversible transformations applied to the cutting area can significantly affect the processing properties, such as balance point stability, as well as various attracting sets formed in its vicinity. Here, the balance point of the dynamic cutting system is considered in the moving coordinates which are determined by the controlled trajectories of the machine executive elements. Both the balance point and the attracting sets characterize elastic deformation shifts of the cutting tip against the workpiece in its contact point with the tool. Therefore, under instability, the formed attracting sets directly affect the workpiece quality parameter. Considering thermodynamic processes allows not only to increase validity of studying the dynamic system of cutting, but also to develop new approaches to the treatment process control.